Memory, Sleep and Dreaming: Experiencing Consolidation - Wamsley, Erin J. (2011)
It is now well established that post-learning sleep is beneficial for human memory performance. At the same time, it has long been known that learning experiences influence the content of subsequent sleep mentation (i.e., “dreaming”). Here, we review evidence that newly encoded memories are reactivated and consolidated in the sleeping brain, and that this process is directly reflected in the content of concomitant sleep mentation, providing a valuable window into the mnemonic functions of sleep.